Local Wisdom as Learning Materials: Character Educational Values of Sundanese Pupuh - Dena Damayanti; Burhan Nurgiyantoro (Intelektual Pustaka Media Utama, 2018)
As character educational values for elementary students deteriorated, the appreciation of Sundanese language by West Javanese people faded. One of many ways to be done was through the use of learning materials in the form of Sundanese pupuh for elementay school students. Pupuh is a literary work in the form of poem in Sundanese language which contains character educational values. This study aimed to describe character educational values in Sundanese pupuh and their relevance as learning materials for elementary school students. Data collection was conducted using the techniques of reading and taking notes of Sundanese pupuh lyrics which contain character educational values, and then identifying the compatibility as elementary school learning materials. The data were analyzed qualitatively, with the steps of: (1) data comparison; (2) data categorization; (3) data presentation; dan (4) inferencing. This study resulted in teamwork as the most occurring value in pupuh Asmarandana, Sinom, Balakbak, Ladrang, Pucung, Lambang, Gambuh, Gurisa, dan Magatru. Thus, this study concluded that Sundanese pupuh had many character educational values relevant to be taught and to be used as learning materials in elementary school.